The travels of a t-shirt in the global economy an economist examines the markets, power and politics of world trade - Rivoli, Pietra (Wiley, 2005)
The Travels of a T-Shirt in the Global Economy takes the reader on a fascinating, around-the-world journey to reveal the economic and political lessons from the life story of a simple t-shirt. Over five years, business professor Pietra Rivoli traveled from a Texas cotton field to a Chinese factory to a used clothing market in Africa, to investigate compelling questions about the politics, economics, ethics, and history of modern business and globalization. Using the story of the t-shirt to illustrate the major issues of the globalization debate, this uniquely entertaining business book offers a surprising, enlightening, and balanced look at one of the major topics of our time.